Etruscan Places, Defiant and Obedient towards Death - Abhik Mukherjee (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Sketches of Etruscan Places, the last and unfinished travel novel of D. H. Lawrence, one of the most controversial writers of twentieth century, offers a unique view of life and death. In this travel book, Lawrence records his phantasmagoric experience about travelling to a dead and fantastic civilisation. Though the civilisation had been brutally annihilated by the Romans and is dead now, it did not succumb to death because of their very pure and magical conception of death. Their sculptures, mainly tomb paintings by Etruscan painters, convey their basic concept of life, love, death, and sex. In the tombs, all the cave paintings were equipped with experimental instruments dedicated to know the reality of life and the mystery of death and to enjoy both of them. The paper attempts to decipher the oxymoronic concepts of death cherished by the ancient Etruscans as interpreted by Lawrence that they tried to transcend death at the deadliest form of the term and, at the same time, to welcome it most.